2020
DOI: 10.1111/grow.12372
|View full text |Cite
|
Sign up to set email alerts
|

Government support and firm innovation performance in Chinese science and technology parks: The perspective of firm and sub‐park heterogeneity

Abstract: Science and technology parks (STPs) are established to promote the firm innovation performance via agglomeration economy and government support in China. On-site qualified firms obtain government R&D funding as a type of government support, and they are offered differential innovation service caused by the differential capabilities of subparks which scatter throughout a single city. It is debatable whether those government supports at firm and sub-park levels can promote firm innovation capabilities. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Since there is a GDP competition among governors, local governments usually publish favorable policies to attract actors and encourage innovation, although those regions may not have advantages in innovation. A study result about Shanghai stands for this argument [40]. Researchers find that governments' R&D input could increase entities' innovation output, but there is a mismatching feature in it.…”
Section: Regional Innovation Systemmentioning
confidence: 99%
“…Since there is a GDP competition among governors, local governments usually publish favorable policies to attract actors and encourage innovation, although those regions may not have advantages in innovation. A study result about Shanghai stands for this argument [40]. Researchers find that governments' R&D input could increase entities' innovation output, but there is a mismatching feature in it.…”
Section: Regional Innovation Systemmentioning
confidence: 99%
“…Unlike the spontaneous agglomeration under the market mechanism seen in most countries, China's HTZs are traction agglomeration zones spearheaded by government policies and local development strategies. The combination of various preferential policies makes the HTZ a policy depression: attracting high-quality innovative talents and innovative capital [26]. On the one hand, the innovation activities of enterprises in the agglomeration zone benefit from special development policies (e.g., low land price and preferential taxes that are lower than those in the external THZs).…”
Section: The Role Of Agglomeration Ability Of Urban Innovation Elementsmentioning
confidence: 99%
“…It has been found to have a positive effect on sales (Liberati et al, 2016), R&D efficiency (Yang & Lee, 2021) and number of university spin-offs within the park (Link & Scott, 2005). Its effect on patents is not clear, with both positive (Teng et al, 2020) and negative (Squicciarini, 2009) effects found. Albahari et al (2018) show park age has a non-linear effect on tenants' innovation performance, with firms in younger and older parks outperforming firms in medium-aged parks.…”
Section: Park Characteristicsmentioning
confidence: 99%